The affective-cognitive learning method (MACPA) - Gladys Molano Caro (Universidad Politécnica Salesiana, 2012)
This paper explores a teaching method that was conceived through the daily interaction with students who were documented by their teachers for not being able to read and write in a timely manner. Although it synthesizes a new way of teaching children and young people to read and write, it also becomes a method for students who are in a "cognitive limbo", who show a learning disability in grasping these key subjects for their educational process.